2019
DOI: 10.1111/rec.12985
|View full text |Cite
|
Sign up to set email alerts
|

A longing for the natural past: unexplored benefits and impacts of a nostalgic approach toward restoration in ecology

Abstract: Nostalgia has endured a negative societal perception since its inception, which influences how it is deployed in ecological restoration. However, the emotion has undergone a paradigmatic shift over the past 15 years with new quantitative psychological research providing insight into complex and oftentimes positive effects. In particular, personal nostalgia can increase social connectedness, optimism, self‐esteem, inspiration, openness, creativity, and charitable giving. Here, we view ecological nostalgia, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Such mixed affective reactions are not uncommon, and previous researchers have demonstrated that it is possible for oppositely valenced emotions to co-occur [ 69 , 70 ]. For instance, in the case of nostalgia, good feelings are elicited through positive memories, but bad feelings because those times have been and gone [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such mixed affective reactions are not uncommon, and previous researchers have demonstrated that it is possible for oppositely valenced emotions to co-occur [ 69 , 70 ]. For instance, in the case of nostalgia, good feelings are elicited through positive memories, but bad feelings because those times have been and gone [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would however appear that this inferential link is predicated by time and place; the two older respondents, having been exposed at least to some extent to Bettelheim's writing and work as part of their training, were inclined to adopt such a position. Nostalgia is regarded as an emotional resource that is used by people to cope with life's challenges, prompting an increase in social connectedness, optimism, self-esteem, inspiration, openness and creativity (Willson, Hart, & Zengel, 2019). For those working in the fields of SEND and children's social care, with its ongoing conceptual and operational debatesas well as politicization and sensitivity to economic conditionsit could be argued that such benefits are an essential contributor to professional well-being.…”
Section: Confirmation Bias and An Unexceptional Estate?mentioning
confidence: 99%
“…As a cognition that produces emotions, nostalgia has been demonstrated to potentially have several positive effects for people who experience it across multiple contexts (Wildschut et al, 2006;Willson et al, 2019;. This corresponds to what many consider to be the media origins of nostalgia, Homer's The Odyssey, where inspired by memories of home, Odysseus was able to gain strength and complete his journey (Hepper et al, 2012).…”
Section: Nostalgiamentioning
confidence: 89%